“‘Stories are in our Bones!’: from mispon to Ācimowin: a conversation with Janine Windolph, in memory of Trudy Stewart” - Sheila Petty; Janine Windolph (Alphaville: Journal of Film and Screen Media)
As Janine and Sheila talk-write this essay-conversation, we combine our positionality as Atikamekw and Woodland Cree storyteller (Janine) and settler Canadian (Sheila), our expertise in screen media production, curation and research, and our dedication to linguistic, cultural, and representational sovereignty in Indigenous art and knowledge production. In Indigenous research practices and approaches to curatorial research and methods, it is important to begin by introducing ourselves. Through this “conversational method of Indigenous inquiry,” (Christian 43), we intend to probe the history of two Indigenous focused film festivals in Saskatchewan – mispon (2006-2018) and Ācimowin (2024-) – and discover how they embrace a methodology of story work, hospitality, and story-gifting to build cultural and representational sovereignty into their curatorial practices and presentation. In concert with this, we will also discuss Janine Windolph’s films, showcased at both festivals, Trudy Stewart’s films and screen work, and their embeddedness in Indigenous representational sovereignty.